2005
DOI: 10.1093/jac/dki370
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of resistance to expanded-spectrum cephalosporins in Escherichia coli isolates recovered in a Spanish hospital

Abstract: Approximately 1.5% of the E. coli isolates of our hospital harboured ESBL genes, those of the CTX-M-9 group being the most common ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
23
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 10 publications
5
23
2
Order By: Relevance
“…One strain had a 2-bp insertion in the ampC promoter spacer region (variant 5) and a plasmid-carried ampC gene; both mechanisms may have contributed to AmpC activity in this strain. The observed ratio of AmpC production due to chromosomal ampC upregulation versus plasmid-mediated AmpC is in accordance with the distribution observed in stud-ies conducted in France, Spain, and Norway (6,14,20). We did not detect any strain that was positive in the genetic analysis and negative in all three phenotypic confirmation tests.…”
Section: Discussionsupporting
confidence: 90%
“…One strain had a 2-bp insertion in the ampC promoter spacer region (variant 5) and a plasmid-carried ampC gene; both mechanisms may have contributed to AmpC activity in this strain. The observed ratio of AmpC production due to chromosomal ampC upregulation versus plasmid-mediated AmpC is in accordance with the distribution observed in stud-ies conducted in France, Spain, and Norway (6,14,20). We did not detect any strain that was positive in the genetic analysis and negative in all three phenotypic confirmation tests.…”
Section: Discussionsupporting
confidence: 90%
“…Many of the P ϩ G Ϫ isolates had ␤-lactam resistance and lacked a bla-CMY-2 gene, which is the most common genetic determinant of expanded-spectrum cephalosporin resistance in Enterobacteriaceae in the United States (15). We found that these isolates had mutations in the promoter and attenuator sequences of the E. coli chromosomal ampC gene that have also been reported from human clinical E. coli isolates in South Africa (39), Spain (7,40), France (12,13,35), Belgium (6), Norway (22), and Denmark (26). They have also been described in animal source E. coli isolates, including those from cattle in Canada (38) and the United Kingdom (34) and pigs in Spain (19) and in E. coli collected from recreational water samples in T A T G T E160 SSuT C A T G T E1026 ASSuTGK T A T G T E1030 ACSSuTKSxtNalRcazAmc T A T G T E1039 ASSuTGKNalRcazAmc T A T G T E1067 ASSuTKCazAmc T A T G T E2534 SSuTGKSxtAmik Canada (37).…”
supporting
confidence: 54%
“…Such resistance mechanisms are prevalent in developing countries, particularly among different Gram-negative and Gram-positive bacteria, due to the availability and affordability of antibiotics like ampicillin, streptomycin, choloramphenicol, tetracycline and trimethoprim/sulphamethoxazole [22]. In addition, resistance to other antibiotics -particularly the new generations of cephalosporins, aminoglycosides and quinolones -has been reported [23][24][25][26][27], along with high rates of extended spectrum β-lactamase and /or Amp-C enzyme production [28]. One explanation for these high resistance rates could be antibiotic usage in the respective institutions.…”
Section: Discussionmentioning
confidence: 99%